Der Einfluss des Bodenpreisniveaus auf die Bebauungsdichte von Wohnareal: Eine empirische Untersuchung in den Kantonen Basel-Landschaft und Zürich - Schmitt, Marcel; Seidl, Irmi (Raumforschung und Raumordnung | Spatial Research and Planning, 2006)
The continued conversion of land into developed areas is mainly propelled by growth in residential housing zones. The question being raised is whether economic policy instruments, such as taxes, can contribute to slowing this land conversion. In order to assess the effects of taxes on the use of land for housing, more information is needed about the extent to which economic agents adapt their consumption of residential building land in the event of price increases. Based on data from the Swiss cantons of Basel-Landschaft and Zurich, this paper investigates whether and to what extent residential housing density is influenced by land price. For the purposes of this study, the selected indicators for residential housing density are the lot size of single-family houses, the ratio of floor space to parcel area (Ausnützungsziffer), and the ratio of realised to maximum floor space to parcel area (Ausbaugrad).